Prevalence, molecular detection, and antimicrobial resistance of Salmonella isolates from poultry farms across central Ethiopia: A cross-sectional study in urban and peri-urban areas - Waktole, H.; Ayele, Y.; Ayalkibet, Y.; Teshome, T.; Muluneh, T.; Ayane, S.; Borena, B.M.; Abayneh, T.; Deresse, G.; Asefa, Z.; Eguale, T.; Amenu, Kebede; et al. (MDPI, 2024)
A cross-sectional study was conducted to assess the prevalence, molecular detection, and antimicrobial resistance of Salmonella isolates within 162 poultry farms in selected urban and peri-urban areas of central Ethiopia. A total of 1515 samples, including cloacal swabs (n = 763), fresh fecal droppings (n = 188), litter (n = 188), feed (n = 188), and water (n = 188), were bacteriologically tested. The molecular detection of some culture-positive isolates was performed via polymerase chain reaction (PCR) by targeting spy and sdfl genes for Salmonella Typhimurium and Salmonella Enteritidis, respectively. Risk factors for the occurrence of the bacterial isolates were assessed. Antimicrobial susceptibility testing of PCR-confirmed Salmonella isolates was conducted using 12 antibiotics. In this study, it was observed that 50.6% of the farms were positive for Salmonella. The overall sample-level prevalence of Salmonella was 14.4%. Among the analyzed risk factors, the type of production, breed, and sample type demonstrated a statistically significant association (p < 0.05) with the bacteriological prevalence of Salmonella. The PCR test disclosed that 45.5% (15/33) and 23.3% (10/43) of the isolates were positive for genes of Salmonella Typhimurium and Salmonella Enteritidis, respectively. The antimicrobial susceptibility test disclosed multi-drug resistance to ten of the tested antibiotics that belong to different classes. Substantial isolation of Salmonella Typhimurium and Salmonella Enteritidis in poultry and on poultry farms, along with the existence of multi-drug resistant isolates, poses an alarming risk of zoonotic and food safety issues. Hence, routine flock testing, farm surveillance, biosecurity intervention, stringent antimicrobial use regulations, and policy support for the sector are highly needed.